A história de Fátima revisitada (1917-1924) - Ramos, Rui (2017)
No other historical event of the twentieth century in Portugal is so systematically and thoroughly documented. The Critical Documentation of Fatima, published by the Sanctuary, is a monument about the nineteenth and twentieth centuries with few parallels in Portuguese erudition. Without leaving history, it is possible to suggest a more interesting context for Fatima than that of “rural religiosity” and that of the simplistic dichotomy between Republics and Church in an equally monolithic and static. This essay, based on the study of primary sources, treats the miracle as a historical event. It means that it does not enter into theological discussions, but that it does not submit itself to conventional sociologism, in its eagerness to eliminate the “happening” and intends to show how the impact of Fatima depended historically on two factors: integration into a national media culture, notably the Lisbon press, and the transformations occurring then both in the Catholic context and in the republicanism.